Detection and Targets Shooter System on Robot Tank with Wireless Controller - Budi Herdiana (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2017)
In this study explained the detection system and shooter target at the robotic tank, a target, a pattern with color detection system that uses the camera as a sensor that will detect the target, when the target has been detected, it will be processed by programming OpenCV, OpenCV will process the results of camera detection using the method of image processing, in which the method of image processing is the most important process for the image processing will be known or recognized by the color and pattern of a pattern that became the basis of the detection in this system, after OpenCV can detect a target then the next step is to send data the results of detection and processed Raspberry Pi, then Raspberry Pi sends a signal to servo controller to drive the servo motor will move to follow where the target is located. System testing is done by experimenting target detection of each color and the distance between the target. Based on test results based color detection system, the system can detect all targets by day and night. The system can also detect the main color when combined with another color, this color combination of testing, the system can detect all primary colors at day and night. As for the different distances blue can detect targets up to a distance of70cm at night and 140cm at day, the green color can detect targets up to a distance of 80cm at night and130cm at day and green colors can detect targets up to a distance of 140cm at night and 150cm at day.Meanwhile for tracking responses, each movement has an average time 2.56125 seconds.